PENCEGAHAN STUNTING DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM BERDASARKAN AYAT AL-QUR’AN DAN HADITS NABI - Nur Kholis; Irma Susan Paramita; Falinda Oktariani (Journal Khafi : Journal Of Islamic Studies, 2025)
Stunting is a serious health issue in Indonesia that affects the quality of human resources. This study aims to examine stunting prevention from the perspective of Islamic Religious Education based on verses from the Qur'an and Hadith. The method used is a literature review with primary data from the Qur'an and Hadith, and secondary data from scientific literature. The findings show that the principles of stunting prevention are outlined in Islamic teachings, such as the recommendation for exclusive breastfeeding (Qur’an, Al-Baqarah: 233; Hadith Abu Dawud), the importance of cleanliness and sanitation (Qur’an, Al-Anfal: 11; Hadith Tirmidhi), the encouragement to work hard to meet family needs (Qur’an, At-Tawbah: 105; Hadith Bukhari), and the consumption of lawful and wholesome food (Qur’an, Al-Baqarah: 168; Hadith Thabrani). This study shows that Islamic teachings offer a holistic approach to health and well-being and can serve as a foundation for religion-based stunting education.